Terminal QRS Distortion on Admission Electrocardiogram as a Predictor of Left Ventricular Systolic Dysfunction in Patients with ST Elevation Myocardial Infarction - Ahsan, Mohammad Morshedul; Akanda, Md Abdul Kader; Hashem, Sabina; Rahman, Md Zillur; Siddiqui, Mohammad Khalilur Rahman; Sultana, Surovi; Reza, Abeeda Tasmin; Datta, Ratan Kumar; Mahmood, Khaled; Karmaker, Pranob (Cardiovascular Journal, 2018)
Background: Increased mortality rates due to coronary artery disease remains a big concern inthe field of cardiology. So early risk stratification is important in daily clinical practice. Risk assessment needs to be done shortly after admission, when only the history, physical examination and the ECG are available. The role of ECG in diagnosis and prognostication of acute myocardial infarction is well established. So this study was done to find out the association of terminal QRS distortion with left ventricular systolic dysfunction in patients with acute ST Elevation Myocardial Infarction. Methods: This prospective observational study was done in NICVD with acute STEMI patients who were eligible for thrombolysis, and was admitted in coronary care unit within 12 hours of onset of chest pain. After considering inclusion and exclusion criteria total 200 acute STEMI patients were taken purposively. 100 patients in group I with terminal QRS distortion and 100 patients in group II without terminal QRS distortion. Then Echocardiography was done to assess left ventricular systolic dysfunction. Results: In our study mean ejection fraction was significantly lower in group I (42.6 ± 5.4% vs 49.7 ± 5.3%, p=0.001).Mean ejection fraction was 40.4± 4.7% in terminal QRS distortion patients with anterior MI and 47.9± 5.9% in patients without terminal QRS distortion with anterior MI (p=0.001).Mean ejection fraction was 46.6± 6.4% in terminal QRS distortion patients with inferior MI and 53.9± 7.8% in patients without terminal QRS distortion patients with inferior MI (p=0.003).Out of the 7 variables location of MI and terminal QRS distortion were found to be the independent predictors for developing left ventricular systolic dysfunction with ORs being 5.20 and 3.21.respectively. Conclusion: ECG on admission in STEMI can predict short term prognosis and help in early assessment of severity of ischemia. Presence of terminal QRS distortion on admission ECG in STEMI is associated with LV systolic dysfunction. So it helps in early decision making for referral to a higher center by our grass root level doctors. Cardiovasc. j. 2018; 11(1): 42-49